Cellular autoimmunity to retinal specific antigens in patients with Behçet's disease. Issue 9 (September 1993) - Yamamoto, J H; Minami, M; Inaba, G; Masuda, K; Mochizuki, M
Abstract : The notion that autoimmune mechanisms play a role in the pathogenesis of certain uveitic conditions in humans is supported by the observation that lymphocytes from such patients respond in culture against retinal specific antigens which are uveitogenic in animals. A large proportion of uveitis patients with Behçet's disease are reported to respond well to S antigen, to interphotoreceptor retinoid binding protein (IRBP) and to several of their uveitogenic peptides, in particular, the S antigen derived peptide M. Patients with Behçet's disease without ocular involvement were reported not to differ in their responses to S antigen from the responses in the control group, yet 35% of them responded to IRBP and approximately two thirds of them responded to the peptides (peptide M, peptide N, R-4, or R-14). The responses were inhibited by monoclonal antibodies to CD4 and to class II MHC HLA-DR molecules. The presence of lymphocyte responses to retinal antigens in patients with Behçet's disease without uveitis might indicate a preclinical stage of ocular involvement. Thus, these data support the idea that autoimmunity to retinal specific antigens may play a role in the ocular inflammation in Behçet's disease.